2005
DOI: 10.1007/s11237-005-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Size Effects in Semiconductor Photocatalysis

Abstract: The characteristics of photocatalytic systems based on nanostructural semiconductors, characterized by quantum size effects, are discussed. An analysis is made of the consequences of exciton quantum confinement in the volume that are significant for photocatalysis and, in particular, the increase in the energy of photogenerated charges with decrease in the particle size, the photoinduced polarization processes, and also the simultaneous display of these effects. Possible ways of further increasing the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 150 publications
(232 reference statements)
2
55
0
1
Order By: Relevance
“…Moreover, a limiting factor that controls the efficiency of photocatalysis is the rapid recombination of photogenerated electrons and holes in semiconductor particles [57]. Recombination of the electron-hole pair within the semiconductor particle is drastically reduced with decreasing particle size [58]. Hence, due to smaller size, recombination rate of electron and hole for the ZnO nanocrystallines prepared in the presence of the RTIL with longer microwave irradiation time and higher RTIL content is lower than the prepared sample in other conditions.…”
Section: Rtil [Emim][etso 4 ] Consists Of [Emim] + Cations and [Etsmentioning
confidence: 99%
“…Moreover, a limiting factor that controls the efficiency of photocatalysis is the rapid recombination of photogenerated electrons and holes in semiconductor particles [57]. Recombination of the electron-hole pair within the semiconductor particle is drastically reduced with decreasing particle size [58]. Hence, due to smaller size, recombination rate of electron and hole for the ZnO nanocrystallines prepared in the presence of the RTIL with longer microwave irradiation time and higher RTIL content is lower than the prepared sample in other conditions.…”
Section: Rtil [Emim][etso 4 ] Consists Of [Emim] + Cations and [Etsmentioning
confidence: 99%
“…Moreover, a limiting factor that controls the efficiency of photocatalysis is the rapid recombination of photogenerated electrons and holes in the nanoparticles [61]. Recombination of electronhole pair within the semiconductor particle is drastically reduced with decreasing particle size [62].…”
Section: Results and Disscusionmentioning
confidence: 99%
“…It is known that the consumption of h VB + in reactions (4) and (6) occurs much more rapidly than the consumption of e CB − in the reaction with oxygen (process (5)) [3,10]. As a result the CdS NP appear to be enriched in negative charge, which leads to the Burshtein-Moss effect, the reversible hypsochromic shift of l tr , the analysis of which permits information to be obtained on the dynamics of reaction (5) in the microsecond domain [3,10,11].…”
mentioning
confidence: 99%
“…As a result the CdS NP appear to be enriched in negative charge, which leads to the Burshtein-Moss effect, the reversible hypsochromic shift of l tr , the analysis of which permits information to be obtained on the dynamics of reaction (5) in the microsecond domain [3,10,11]. For example, using the Burshtein-Moss effect the authors of [11] showed that the rate of reaction (5) increased by an order of magnitude with a decrease in the size of CdS NP from 7.2 to 3.2 nm.…”
mentioning
confidence: 99%